Effective Tooth Brushing Techniques Based on Periodontal Tissue Conditions : A Narrative Review - Pindobilowo; Umi Ghoni Tjiptoningsih; Dwi Ariani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Introduction: Tooth brushing becomes ineffective if done with the wrong technique and not adapted to the condition of the periodontal tissue. Objective: To know the effective tooth brushing technique based on the condition of the periodontal tissue. Method: This literature study uses the Narrative Review method. References were collected, namely journals through the BMC Oral Health database, PubMed, and Google Scholar. Conclusion: The brushing methods that have been introduced have been shown to be effective in removing plaque, especially with the right technique. However, if the technique is wrong and not adapted to the condition of the periodontal tissue, it will have a negative impact because the dental plaque will not be completely cleaned.